2020
DOI: 10.1103/physrevd.102.043513
|View full text |Cite
|
Sign up to set email alerts
|

Cross-correlation of the astrophysical gravitational-wave background with galaxy clustering

Abstract: We investigate the correlation between the distribution of galaxies and the predicted gravitational-wave background of astrophysical origin. We show that the large angular scale anisotropies of this background are dominated by nearby nonlinear structure, which depends on the notoriously hard to model galaxy power spectrum at small scales. In contrast, we report that the cross-correlation of this signal with galaxy catalogues depends only on linear scales and can be used to constrain the average contribution to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 56 publications
0
41
0
Order By: Relevance
“…The background may also include signals of cosmological origin, i.e., produced in the early Universe during an inflationary epoch [19][20][21][22][23][24][25][26][27], or as a direct result of phase transitions [28][29][30], primordial black hole mergers [31][32][33][34], or other associated phenomena [35]. Different models could, in principle, be distinguished by characteristic features in the angular distribution [36][37][38][39][40][41][42][43][44][45][46][47]. For example, cosmic strings have an angular power spectrum which is sharply peaked at small multipoles [48,49], while neutron stars in our Galaxy would trace out the Galactic plane [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…The background may also include signals of cosmological origin, i.e., produced in the early Universe during an inflationary epoch [19][20][21][22][23][24][25][26][27], or as a direct result of phase transitions [28][29][30], primordial black hole mergers [31][32][33][34], or other associated phenomena [35]. Different models could, in principle, be distinguished by characteristic features in the angular distribution [36][37][38][39][40][41][42][43][44][45][46][47]. For example, cosmic strings have an angular power spectrum which is sharply peaked at small multipoles [48,49], while neutron stars in our Galaxy would trace out the Galactic plane [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…Note that our analysis differs significantly from Ref. [17], where the constraints derived on posterior distributions are only cosmic variance limited.…”
Section: Resultsmentioning
confidence: 68%
“…and by construction we have 1 + ∆ G p = 1 as ∑ r W (r) dr = 1. Assuming purely Poisson statistics for both N G r,p and N L GW r,p , we can now compute the variance of the different auto-and cross-correlations [17]. AGWB auto-correlation:…”
Section: B Agwb-galaxy Count Cross-correlations and Shot Noisementioning
confidence: 99%
“…This is analysed in [123,124] for the anisotropic background, and it is found that the white noise component dominates current LIGO and Virgo detectors; however, the planned upgrades of these detectors and the future 3G detectors may be sufficient to curb this effect. As discussed in [125,126], another strategy to mitigate the shot noise is to cross-correlate the GW signal with a galaxy catalogue, as this cross-correlation spectrum has a much lower level of shot noise. Furthermore, as GW sources are finite in time, then Poisson statistics dictate that this noise decays as the inverse of the observation time; hence, long observing runs will progressively mitigate this effect.…”
Section: Observational Properties Of Stochastic Backgroundsmentioning
confidence: 99%